Load frequency control of power systems with penetration of renewable energy sources - Chin, Yi Ming (Nanyang Technological University, 2022)
With the swift advancement in technology, our reliance for electrical system has risen at a commensurate rate. In a power system, the loads are always changing due to uncertain demands from consumers. There is a causality with regards to changing load demand and frequency. If the total generation power is more than the load demand, frequency will rise and vice versa. The fluctuation of frequency will cause the power system to experience instability. If the disparity of frequency is too huge, consumers will experience power outage which will bring many inconveniences in our modern world.